Rare Case of Young Patient with Intraventricular Angiomatous Meningioma - Heemann, Gabriel Carvalho; Paglioli, Rafael Silva; Wainberg, Ricardo Chmelnitsky (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2017)
Pediatric meningiomas are rare and account for only 2.2% of the central nervous system (CNS) tumors. In this age group, they are more frequently located in atypical sites, such as, mainly, the ventricular system, with a frequency of 8.8 to 13.6%. Adding this to the fact that the angiomatous subtype constitutes only 2.1% of all meningiomas, the rarity of the case reported here is corroborated. We report a 17-year-old female patient diagnosed with intraventricular angiomatous meningioma; she underwent surgical resection of the tumor in the body and frontal horn of the right lateral ventricle, and there were no neurological sequelae. With a follow-up of 26 months, there was no recurrence and the patient had clinical stability. Intraventricular tumors usually have slow growth and reach a considerable size until they cause symptoms and then are diagnosed. In addition, the deep location of the tumor and its proximity to eloquent areas make these tumors a neurosurgical challenge. The angiomatous subtype, due to the presence of hypervascularization (consisting of > 50% of vascular components), may, in some cases, hinder surgical resection as well as be erroneously diagnosed. However, surgical treatment aimed at total resection of the lesion remains the conduct of choice in the case reported here, especially in patients in the first two decades of life, in which the use of radiation is avoided. Specifically when it comes to the surgery, we chose a transcalosal approach that allows a good transoperative visualization of the lesion when located in the body and frontal horn of the lateral ventricle.
Keywords: meningioma; intraventricular neoplasms; pediatrics; lateral ventricles